Understanding Racism in a Post-Racial World Visible Invisibilities - Kamaloni, Sunshine; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book addresses the question, how can we talk about race in a world that is considered post-racial, a world where race doesn't exist? Kamaloni engages with the tradition of everyday racism and traces the process of racialisation through the interaction of bodies in space. Exploring the embodied experience exposes the idea of post-racialism as a response to continued cultural anxieties about race and the desire to erase it. Understanding Racism in a Post-Racial World presents a broader question about what everyday encounters about race might tell us about the current cultural construction of race. The book provides a much-needed investigation of the intersection of race, bodies and space as a critical part of how bodies and spaces become racialised, and will be of interest to students and scholars interested in understanding and discussing race across interdisciplinary areas such as cultural studies, communication, gender studies, geography,body studies, literature studies and urban studies. .
Chapter 1. Introduction -- Chapter 2. 'Where Did You Come From (You Black Bitch)?' - Australia and Racism -- Chapter 3. 'Can I Touch You?' - Everyday Racism -- Chapter 4. 'What Are You Doing Here?' - The Politics of Race and Belonging at the Airport -- Chapter 5. 'Is There Someone Else I Can Talk to?' - Raced Bodies at Work -- Chapter 6. 'What Do You Have There?' - Carrying Race in My Shopping Basket -- Chapter 7. Conclusion.
Keywords: Race; Culture; Sex; Race and Ethnicity Studies; Sociology of Culture; Gender Studies